α-Substituted Lactams and Acetamides: Ion Channel Modulators that Show Promise in Treating Drug-resistant Epilepsy - Krivoshein, Arcadius V. (Central Nervous System Agents in Medicinal Chemistry, 2020)
The two main problems in the pharmacotherapy of epilepsy are resistance to currently available first-line medications (which occurs in about one third of patients) and the high incidence of side effects. To address these two challenges, extensive efforts are being undertaken to design new, structurally distinct antiepileptic drugs with a broad spectrum of anticonvulsant activity. Tests in animal models of epilepsy indicate that α-substituted lactams and acetamides show a broad spectrum of anticonvulsant activity (including very promising activity in drug-resistant models) as well as an excellent safety profile. Limited clinical results confirm these preclinical findings. In the first part of this review, pharmacology and toxicology of α-substituted lactams and acetamides and their putative protein targets in the brain have been discussed. This is followed by a discussion of structure-activity relationships among α-alkyl-, α-aryl-, and α-aryl-α-alkyl-substituted derivatives. The most promising structures seem to be those related to 3-ethyl-3-phenylpyrrolidin-2-one, 2-phenylbutyramide, and 2- sec-butylvaleramide. The information presented in this review is expected to facilitate rational drug design and development efforts for α-substituted lactams and acetamides.
Keywords: ion channels